Analisis Resepsi Penggemar K-Drama terhadap Adaptasi A Business Proposal Versi Indonesia - Salwia, Salwia; Gibbran Prathisara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the audience reception of K-Drama fans toward the Indonesian adaptation of A Business Proposal. The research employs a qualitative approach using reception analysis based on Stuart Hall’s theory, particularly through the concepts of encoding and decoding. Data were collected through in-depth interviews with ten informants who are active K-Drama viewers. The findings indicate that audience interpretations are diverse and are influenced by their experience of watching the original version, expectations toward the adaptation, as well as their social and cultural backgrounds. The analysis identifies three decoding positions: dominant, negotiated, and oppositional. The dominant position is reflected in audiences who accept the intended meaning constructed by the producers and perceive the adaptation as still relevant within the local context. However, the negotiated and oppositional positions are more prevalent. In the negotiated position, audiences accept the core narrative but express criticism toward emotional delivery, dialogue, and production quality. Meanwhile, the oppositional position reflects a rejection of the adaptation, as it is perceived as failing to adequately represent the essence of the original version. These findings confirm that audiences play an active role in interpreting media texts.